Conservação da energia mecânica : uma sequência didática inspirada na ideia de UEPS - Silva, Renato Peron da (Universidade Federal de São Carlos, 2016)
This study aims to propose a didactic sequence involving the use of resources and diversified activities applied to the teaching of Conservation of Mechanical Energy and its applications. The didactic sequence was based on the Theory of Meaningful Learning and the idea of concept maps, taking into consideration the principles and present steps in Potentially Meaningful Teaching Units (PMTU). In the didactic sequence of concepts approach is through reading popular science short texts involving different contexts and applications, through an animation and a computer simulation, using questionnaires, including a mathematical formalization, and the use of conceptual maps. The elaborate didactic sequence was implemented in a class of 1 st year of high school, in a private school in the city of Ribeirão Preto, SP. In general, the application of the teaching sequence obtained good results. In addition to satisfactory learning outcomes, it was noticed the involvement of students in the proposed activities, showing satisfied with the dynamics of classes, and even explaining that they facilitated the understanding of the study content, especially those involving conceptual and computing resources maps. From the results, it is understood that the educational product developed, a didactic sequence guided by the idea of PMTU, has a potential in terms of promoting the learning of mechanical energy conservation concepts can be implemented in other contexts.
Keywords: Conservação de energia mecânica; Mapas conceituais; UEPS; Aprendizagem significativa; Conservation of mechanical energy; Conceptual maps; PMTU; Meaningful learning; CIENCIAS EXATAS E DA TERRA::FISICA